2018
DOI: 10.1172/jci122631
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental immune modulation with a bacterial-derived agent protects against allergic airway inflammation

Abstract: Chronic allergic inflammatory diseases are a major cause of morbidity, with allergic asthma alone affecting over 300 million people worldwide. Epidemiological studies demonstrate that environmental stimuli are associated with either the promotion or prevention of disease. Major reductions in asthma prevalence are documented in European and US farming communities. Protection is associated with exposure of mothers during pregnancy to microbial breakdown products present in farm dusts and unprocessed foods and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(82 citation statements)
references
References 72 publications
15
67
0
Order By: Relevance
“…Previous studies from our laboratory have additionally identified postnatal expansion of bone marrow myeloid progenitor (MP) cell populations as an effect of maternal treatment with OM-85 during pregnancy (8). Based on these findings, we hypothesised that the enhanced cDC population within fetal bone marrow following maternal OM-85 treatment would also be accompanied by concomitant upregulation of upstream MP subsets.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies from our laboratory have additionally identified postnatal expansion of bone marrow myeloid progenitor (MP) cell populations as an effect of maternal treatment with OM-85 during pregnancy (8). Based on these findings, we hypothesised that the enhanced cDC population within fetal bone marrow following maternal OM-85 treatment would also be accompanied by concomitant upregulation of upstream MP subsets.…”
Section: Resultsmentioning
confidence: 88%
“…In summary, the data presented here builds on forerunner human (4,24) and experimental animal (8,34,35) studies providing evidence that non-pathogenic maternal microbial-associated exposures during pregnancy can be transcribed transplacentally into beneficial immune training signals for the developing fetus. We provide direct evidence that maternal OM-85 treatment during pregnancy transplacentally accelerates functional immunocompetence of fetal bone marrow cDCs and for the first time identify the transcription factor XBP1 as a putative driver of this immune training mechanism.…”
Section: Nk Cells and Cd3 + T Cells (Supplementalmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, exposure to farm animal shed during pregnancy is also a major factor in modifying immune function and reducing risk of allergic disease in offspring (3) and correlates with enhanced induction of cord blood T regulatory cells (67). When modeled in mice, in a maternal TLR-dependent manner, endotoxin exposure during pregnancy ameliorates allergic sensitivities in the progeny of exposed dams (68) and increases tracheal Treg percentages (69). Conversely, anti-helminth therapy given during pregnancy correlates with increased allergic eczema in newborns, suggesting immune training afforded by the maternal environment impacts immunity to unrelated antigens (70).…”
Section: Hygiene Hypothesis Revisited-a Prenatal Window Intersected Bmentioning
confidence: 99%
“…As such, a degree of emphasis was placed on effector, regulatory and memory subsets within T-cell and B-cell populations. In regards to Tcells, the conversion of peripheral naïve CD4 + T-cells to T-effector (Teff) cells is denoted by upregulation of the activation marker CD25, while concomitant upregulation of both CD25 and intracellular Foxp3 expression is essential for the peripheral induction of regulatory T cells (Treg) 7 , a process previously recognised in the protection against allergic airways inflammation following microbial-derived immunomodulation 8,9 . Furthermore, the expression of CD44 on splenic Treg has been implicated in promoting enhanced function 10 .…”
Section: Introductionmentioning
confidence: 99%